2015
DOI: 10.1128/jvi.01741-15
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Pathway of HIV-1 Resistance to Novel Fusion Inhibitors Targeting the Gp41 Pocket

Abstract: The peptide drug enfuvirtide (T20) is the only HIV-1 fusion inhibitor in clinical use, but it easily induces drug resistance, calling for new strategies for developing effective drugs. On the basis of the M-T hook structure, we recently developed highly potent short-peptide HIV-1 fusion inhibitors (MTSC22 and HP23), which mainly target the conserved gp41 pocket and possess high genetic barriers to resistance. Here, we focused on the selection and characterization of HIV-1 escape mutants of MTSC22, which reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…So far, we have failed to induce HIV-1 mutants resistant to HP23 during in-vitro selection, different from its templates SC22EK and MTSC22 [36,37]. The L57R mutation located in the deep gp41 pocket site was selected by MTSC22, which might correlate with the M-T hook structure [37]. Although LP-11 could not efficiently inhibit the L57R mutant, we think that it has a higher genetic barrier to developing 1194 AIDS 2016, Vol 30 No 8 resistance, similar to its template HP23.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…So far, we have failed to induce HIV-1 mutants resistant to HP23 during in-vitro selection, different from its templates SC22EK and MTSC22 [36,37]. The L57R mutation located in the deep gp41 pocket site was selected by MTSC22, which might correlate with the M-T hook structure [37]. Although LP-11 could not efficiently inhibit the L57R mutant, we think that it has a higher genetic barrier to developing 1194 AIDS 2016, Vol 30 No 8 resistance, similar to its template HP23.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, we demonstrated that HP23 is a potent fusion inhibitor with a high genetic barrier [17]. So far, we have failed to induce HIV-1 mutants resistant to HP23 during in-vitro selection, different from its templates SC22EK and MTSC22 [36,37]. The L57R mutation located in the deep gp41 pocket site was selected by MTSC22, which might correlate with the M-T hook structure [37].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We also constructed a panel of 15 HIV-1 NL4-3 -based pseudoviruses with Envs carrying T20-or HP23-resistant mutations (43,44). The inhibition data in Table 4 showed that (i) the long peptides T20 and P3 exhibited relatively higher resistance on T20-resistant mutants, but the short peptides HP23 and 2P23 could maintain their potency, and (ii) 2P23 also displayed improved inhibition over some HP23-resistant mutants (e.g., L57R and L57R/E136G).…”
Section: Short-peptide Fusionmentioning
confidence: 99%
“…As shown in Table 1 We also constructed two panels of inhibitor-resistant pseudoviruses using NL4-3 Env as a template. The panel 1 Envs were introduced with single or double mutations that rendered resistance to T-20, while the panel 2 Envs were generated to carry HP23-resistant mutations (21,22). The data in Table 1 LP-19 has strong and long-acting ex vivo antiviral activity.…”
Section: Generation Of a Highly Stable Lipopeptide-based Hiv Fusion Imentioning
confidence: 99%